ANALISIS PENGARUH MODAL DAN UPAH TERHADAP PENYERAPAN TENAGA KERJA EKONOMI KREATIF SEKTOR MUSIK - Muttaqien, Achmad Muizzul; Fadjar, Nurman Setiawan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This study aims to determine the influence of capital and wages on the level of labor absorption in the creative economy industry of the music sector in Malang City. This research used a descriptive approach with quantitative methods. The dependent variable in this study was the respondent's music industry workforce. This study establishes two independent variables, namely wages and capital. The population in this study is all music industry workers in Malang City. Therefore, the number of samples to be taken in as many as 97 people. Data collection techniques through questionnaires. Data analysis techniques are carried out through descriptive analysis, classical assumption testing, hypothesis testing, and multiple linear test analysis. The results showed that 1) there is a joint (simultaneous) influence of free variables on the variable of acceptable Labor Absorption, 2) capital (X1) has a significant influence on Labor Absorption, 3) variables in wage levels (X2) which have a significant influence on the absorption of labor in the music industry in Malang City, and 4) variables wage levels have the most decisive influence compared to other variables, then variables Wage levels have a dominant influence on the absorption of music industry labor in Malang City